Control of Indirect Matrix Converter by Using Improved SVM Method - Lavanya Nannapaneni; M Venu Gopala Rao (Bulletin of Electrical Engineering and Informatics, 2015)
A novel space vector modulation (SVM) method for an indirect matrix converter (IMC) is used to reduce the common -mode voltage (CMV) in the output. The process of selecting required active vectors and to describe the switching sequence in the inverter stage of the IMC is explained in this paper. This novel SVM method used to decrease the peak -to-peak amplitude voltage of CMV without using any external hardware. The other advantage of this SVM method is to reduce the total harmonic distortion of line-to-line output voltage. This new modulation technique is easily implemented through simulation and its results are used to demonstrate the improved performance of the input/output waveforms.